Mapeamento espectroscópico de propriedades físicas dos remanescentes de supernova N49 e N11L - Pauletti, Diogo (2015)
Supernova remnants allow to derive many physical properties of the medium where they lie, such as temperature, density and chemical abundances. Some of the physical characteristics of these objects may differ significantly if one compares different samples, depending on the formation mechanisms, evolutionary stages and characteristics of the local medium. Even in a single object, properties can vary substantially along its extension. Nevertheless, most of the published spectroscopic works about supernova remnants use integrated data or data from the brightest positions. Such data do not allow to determine the physical conditions all over the object and are little useful for studying its structure and evolution modeling. This work presents a study of supernova remnants based on the spectroscopic mapping of their physical properties. The long-slit spectroscopy technique was used to accomplish data from all the targets extension, the supernova remnants N49 e N11L from the Large Magellanic Cloud. The data were acquired with the 4,1 m SOAR telescope. For N11L, the principal lines were mapped and the electron density map was obtained from the line intensity ratio [S II] λ6716/λ6731 for the spectra with and without sky subtraction. The last one produced values on almost all the observed region (N11L and its vicinity). The electron density varies between minimal values to values a bit larger than 300 cm−3 . For N49, the map of values of the electron density were built and for the electron temperature from four different sensors: [O III] (λ5007+λ4959)/λ4363, [S II] (λ6716+λ6731)/λ4068,76, [O II] λ3727/(λ7320+λ7330) and [N II] (λ6583+λ6548)/λ5755. 67 emission lines were measured in many positions, allowing to built maps of fluxes and flux ratios. Other 17 weaker lines were measured only in the integrated spectra. Among the 84 measured lines, about 20 were measured for the first time in this remnant. N49 presents a strong density gradient, varying from a few dozens electrons per cubic centimeter on the northwest region to values about 6 000 cm−3 on the southwest. The temperature distribution obtained via [O III] sensor presents higher values in the centre (∼ 40 000 K). The other temperature maps do not present the same characteristic and have temperature values about 11 000 K. The variation of the logarithmic extinction coefficient c(Hβ) in different portions of the nebula was investigated analyzing the first three Balmer decrements. This analysis suggested that collisional excitation of the Hα may be present in the boundary regions of N49. Diagnostic diagrams with line intensity ratio of this work are compared with theoretical data obtained from the MAPPINGS III code. Various line intensity ratio maps presented values with radial variations. The analysis of this behavior suggests that it is related with a variation of the gas velocity, which has smaller values on the farthest regions.